Disparities in Mental Health Service Use of Racial and Ethnic Minority Elderly Adults. Issue 1 (18th December 2012) - Jimenez, Daniel E.; Cook, Ben; Bartels, Stephen J.; Alegría, Margarita
<x xml:space="preserve">Abstract</x> Objectives To apply the Institute of Medicine definition of healthcare disparities, to measure disparities in different aspects of episodes of mental health care and to identify disparities in types of mental health services used. Design Four 2‐year longitudinal datasets from Panels 9 to 13 (2004–2009) of the Medical Expenditure Panel Surveys were combined. Setting Large‐scale surveys of families and individuals and their medical providers across the United States. Participants One thousand six hundred fifty‐eight participants (981 white, 303 black, and 374 Latino) aged 60 and older with probable mental healthcare needs. Measurements Mental healthcare need was defined as a Kessler‐6 Scale score >12 and a Patient Health Questionnaire‐2 score >2. Five aspects of mental healthcare episodes were analyzed: treatment initiation, adequacy of care, duration of care, number of visits, and expenditures. Whether episodes of care included only prescription drug fills, only outpatient visits, or both was assessed. Results Treatment initiation and adequacy were lower for blacks and Latinos than whites. Latinos experienced episodes of longer duration, more visits, and higher expenditures. Blacks and Latinos had significantly lower rates of episodes that consisted of only medication refills. Blacks had significantly greater rates of episodes with only outpatient care visits. Latinos had significantly higher rates of medication plus outpatient visits. Conclusion Low mental health treatment initiation and poor adequacy suggest the need for culturally appropriate interventions to engage older blacks and Latinos in mental health care. The surprising findings in blacks (higher rates of outpatient care visits) and Latinos (higher rates of medication plus outpatient visits) highlight the complexities of the older adult population and suggest new avenues for disparities research.